Description of a new Charinus species (Amblypygi: Charinidae) from the Monseñor Nouel province, Dominican Republic - Seiter, Michael; Schramm, Frederic D.; Schwaha, Thomas (Zootaxa, 2018)
A new species of Charinus Simon, 1892 from the Dominican Republic is described. With the addition of Charinus magua sp. nov. from the Monseñor Nouel province, the number of known members of the genus Charinus occurring on the island Hispaniola is increased to three. The frontal process, the trichobothria on leg IV, the number and shape of the articles of leg I and the shape of the tarsomers of legs II–IV are often included in taxonomical descriptions of Charinus species. We present these characters in the detailed description of C. magua sp. nov. and illustrate these for the first time for the two other known Charinus from Hispaniola, Charinus dominicanus and Charinus bahoruco. Furthermore, we present and discuss the cerotegument ultrastructure of all three species.